Interdigitating Elastic Fibers with a Liquid Metal Core toward Ultrastretchable and Soft Capacitive Sensors: From 1D Fibers to 2D Electronics - Lee, Sangmin; Bhuyan, Priyanuj; Bae, Kwak Jin; Yu, Jaesang; Jeon, Hongchan; Park, Sungjune (AMER CHEMICAL SOC, 2022)
Ultrastretchable and elastic fibers with a liquid metal (EGaIn, eutectic alloy of gallium and indium) core were utilized to fabricate 2D capacitive sensors by arranging the fibers in an interdigitated structure. Once the fibers were prepared by simple roller coating, interdigitated structures were formed by plasma-activated chemical bonding of the fibers. EGaIn was injected into the core of the hollow elastic fibers, resulting in 2D capacitive sensors with dielectrics between the in-plane inter digitated electrodes. The liquid metal used in this work preserves the metallic conductivity upon strain because of the fluidic nature of the metal. Thus, the capacitance can be manipulated by the strain (upon mechanical deformation) of interdigitated fibers. The out-of-plane fringe electric field generated at the edges of the in plane interdigitated liquid metal electrodes can be interfered with by adjacent objects or solvents surrounding the fibers due to various dielectric constants of the medium, resulting in a varying capacitance. This approach of fabricating 2D capacitive sensors from 1D fibers with a liquid metal core can be implemented in electronic textiles, wearable sensors, and soft robotics, owing to the fiber-form factor as well as the deformable electrical conductivity of the liquid metal wire.